PEMBUATAN PROTOTIPE EXHAUST FAN OTOMATIS MENGUNAKAN SENSOR SUHU DHT11 UNTUK APLIKASI DIKENDARAAN DAN RUANGAN BENGKEL - Setiawan, Tia (Universitas Majalengka, 2022)
Design of an automatic exhaust fan prototype using a DHT11 temperature sensor is the manufacture of an electronic device to lower the temperature in a room and suck air in the room to be discharged outside the room, at the same time the exhaust fan draws fresh air outside into the room. In addition, the exhaust fan can also circulate air in a room, in order to stay healthy the room needs air circulation so that there is always a change of indoor air with fresh air from outside. This tool works automatically because this tool uses a temperature and humidity sensor type DHT11. This tool is still being made in the form of a prototype or initial model which is an example before making the actual tool. In this prototype, room temperature and humidity data are detected by the DHT11 sensor. The DHT11 temperature sensor detects the room temperature, then it is processed by the microcontroller then the exhaust fan will rotate to suck air out of the room by providing a calibrated digital signal. 30-50°C and a relative humidity measurement range of 20-90%. The input voltage is 12 volts and 5 volts is changed by the power supply. Arduino microcontroller works at a voltage of 5 volts and a voltage of 12 volts for the relay circuit and the exhaust fan will turn on at a temperature of more than 30 ° if the temperature is less than 30 ° C then the exhaust fan must stop rotating.